Implementation of Archives Digitization Policy as a Form of Implementation of an Electronic-Based Government System - Syarif Makmur (Journal of Social Research, 2023)
The Indonesian government has adopted the concept of electronic-based government to improve the efficiency and effectiveness of governance. One important aspect of electronic-based governance is the digitization of archives, which will help improve the accessibility, security, and readability of government documents. However, the implementation of archive digitization in Indonesia is still constrained by several factors, such as lack of understanding of technology and lack of support from government management. The purpose of this study is to analyze, review and find out whether the Presidential Regulation of the Republic of Indonesia number 95 of 2018 concerning the Electronic-Based Government System (SPBE) has been effectively implemented by all Institutions, Ministries and Regional Governments. The next objective is to analyze, review and find out whether the implementation of archive digitization policies in all ministries, institutions and local governments is effective and significant in governance. The research method used is a qualitative approach through observation, literature study and observation of the phenomenon of digital archives in all levels of central and regional governments. Analysis and discussion in this study were carried out on the Variables of Digitization of archives and variables of Effectiveness of Archival Administration. The results obtained in this study that the digitization of archives in all institutions, ministries and local governments contributes significantly to the administration of government. The conclusion from the results of this study is that Presidential Regulation number 95 of 2018 concerning Electronic-Based Government Systems has not been optimally implemented. Digitization of archives is a strategy to save budget, human resources and workspace and digitization of archives contributes significantly to the administration of government.